2003
DOI: 10.1095/biolreprod.102.011312
|View full text |Cite
|
Sign up to set email alerts
|

Donor-Dependent Developmental Competence of Oocytes from Lambs Subjected to Repeated Hormonal Stimulation1

Abstract: An unpredictability of ovarian response still remains the major problem concerning ovine reproductive programs. The influence of several environmental, genetic, and ovarian cycle effects on oocyte/embryo yield from donor females has been previously reported. The present research has been designed to exclude aforementioned causes of variability, thus to verify embryogenic competence in homogenous groups of animals. For this purpose we used prepubertal ewes kept under identical conditions. Initially, we stimulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
27
2

Year Published

2004
2004
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(35 citation statements)
references
References 42 publications
6
27
2
Order By: Relevance
“…In this study, the treatment of animals with a progestagen (fluorogestone acetate (FGA)), a short while after ovulation, most likely led to an increase in the production of transferable embryos and to improve the repeatability by reducing the deleterious effect of the early regression of CL on embryos (Cervantes et al 2007). The observed high within-animal repeatability indicated that embryo production capacity is intrinsically dependent on the donor goat and agrees with data obtained for cows (Tonhati et al 1999, Asada & Terawaki 2002, Benyei et al 2004, Peixoto et al 2004, Monniaux et al 2010 and sheep (Ptak et al 2003).…”
Section: Discussionsupporting
confidence: 81%
“…In this study, the treatment of animals with a progestagen (fluorogestone acetate (FGA)), a short while after ovulation, most likely led to an increase in the production of transferable embryos and to improve the repeatability by reducing the deleterious effect of the early regression of CL on embryos (Cervantes et al 2007). The observed high within-animal repeatability indicated that embryo production capacity is intrinsically dependent on the donor goat and agrees with data obtained for cows (Tonhati et al 1999, Asada & Terawaki 2002, Benyei et al 2004, Peixoto et al 2004, Monniaux et al 2010 and sheep (Ptak et al 2003).…”
Section: Discussionsupporting
confidence: 81%
“…Similar results have been reported by Al-Kamali et al (25) in ewes. This is in accordance with Ptak et al (29), who found that follicular response declined with repeated stimulation. Therefore, the decrease in ovulations and transferable embryos after repeated treatments might be caused by genital tract adhesion after repeated flushings.…”
Section: Discussionsupporting
confidence: 93%
“…Similar results were obtained in nuclear maturation rates: 67.75% in M1 and 73.18% in M2; however, the amplitude differences were statistically lower than those observed previously in cumulus cell expansion rates (p < 0.05). It has been shown that oocyte donor breed affects its developmental competence in other species (Ptak et al, 2003;Rátky et al, 2005). However, our results were within the average rates previously reported in other cattle breeds (Camargo et al, 1997;Kafi et al, 2002;Wang et al, 2007;McLaughlin & Telfer, 2010;Nicodemo et al, 2010).…”
supporting
confidence: 87%